(untitled) (Journal of Scientific Research, 2024)
The fundamental understanding of drug-water interaction is pivotal to ensure the bioavailability of a drug as it depends on the solubility profile of the drug candidate. The present work is undertaken to investigate the molecular interaction between a non-steroidal anti-inflammatory drug, Ibuprofen, and water molecule at the atomic level using Density Functional Theory. Gaussian 09W software is used to optimize the molecules using the Becke–Lee–Yang–Parr/6-31 G (d, p) level. The newly formed intermolecular hydrogen bonds O34-H36—O1 (2.58 Å) and O34-H35—O2 (2.08 Å) dominate the Raman spectra of the compound in the higher wavenumber region, and a remarkable spectral shift is observed in the interacting state. NBO analysis validates the transfer of charges in the interacting state via O-H—O with a stabilization energy of 35.32 kcal/mol. AIM analysis reveals the existence of a moderate (O34−H35∙∙∙O2) and a weak hydrogen bond (O34−H36∙∙∙O1) between the two monomers. The compound’s experimentally recorded UV absorption spectrum exhibits an absorption peak at 216.59 nm. The corresponding energy gap of 5.72 eV agrees with the calculated energy gap of the interacting state (5.90 eV). MEP surface of the ibuprofen + Water is evaluated, which will further help in biological recognition.